Image Plagiarism Control System in Academic Articles - Oluk, Sabahattin; Kaya, Buket (Ali KARCI, 2022)
Similarity (plagiarism) control in pictures has become important because the information content of the pictures increases day by day and the copyrights become widespread. Currently, there are software that detects text-based similarity in academic studies, and no similarity detection can be made regarding the pictures in these studies. In academic studies, when citing ideas and texts and citing a bibliography, it is necessary to cite pictures (tables, results, graphics, etc.) in the same way. In this study, image hashing method was used to determine similarity in pictures. There are many methods and methods for detecting similarity in pictures. It has been determined that the most suitable method for the system to be built is perceptual hashing. Traditional image processing methods have a high success rate at this point, and as a disadvantage, it is not preferred because it is thought to have a negative effect on the system speed.

Resimlerde benzerlik (intihal) kontrolü resimlerin her geçen gün bilgi içeriğinin daha fazla artması ve telif haklarının yaygınlaşmasından dolayı önemli bir hale gelmiştir. Hali hazırda yapılan akademik çalışmalarda metin tabanlı benzerlik tespiti yapan yazılımları bulunmakta olup bu çalışmalardaki resimler ile ilgili olarak bir benzerlik tespiti yapılamamaktadır. Akademik çalışmalarda ne kadar fikirler ve metinler alınırken atıf yapılıp kaynakça göstermek gerekir ise resimler (tablolar, sonuçlar, grafikler vb.) alınırken de aynı şekilde atıf yapılıp kaynak gösterilmelidir. Bu çalışmada resimlerde benzerlik tespiti için resim hashleme (image hashing) yöntemi kullanılmıştır. Resimlerde benzerlik tespiti için birçok yöntem ve metot bulunmaktadır. Yapılacak sistem için en uygun yöntemin Algısal Kıyım (Perceptual Hashing) olduğu tespit edilmiştir. Geleneksel görüntü işleme metotlarının bu noktada başarı oranının yüksek olmasının yanında dezavantaj olarak sistem hızına negatif yönde bir etki sunacağı düşünülüp gözlemlendiği için tercih edilmemiştir.
Akademik Yazılarda Resim İntihal Kontrolü Sistemi
Keywords: Computer Software; Bilgisayar Yazılımı